Pengaruh Senam Diabetes Mellitus terhadap Nilai Gula Darah pada Penderita Hiperglikemi : (di Dusun Putuk Desa Banaran Kecamatan Kandangan Kabupaten Kediri) - Hakim Tobroni HR; Berna Detha Meilyana (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
He primary issue in hyperglycemia is insulin resistance, a condition where the body becomes less responsive to insulin, preventing glucose from being effectively absorbed by cells. One method to address insulin resistance in patients is through physical activities such as exercise. This study aims to analyze the impact of diabetes mellitus exercises on blood glucose levels in patients with hyperglycemia. This study employed a One Group Pretest-Posttest design with a Cross-Sectional approach. The population consisted of all hyperglycemia patients in Dusun Putuk, Banaran Village, Kandangan Subdistrict, Kediri Regency, totaling 50 respondents. The study sample included 44 hyperglycemia patients selected using the Simple Random Sampling method. The independent variable was diabetes mellitus exercises, while the dependent variable was blood glucose levels, measured using a glucose test device. Data processing involved editing, coding, and tabulation. Data analysis was conducted using the Wilcoxon Test. The results showed that, before the exercises, blood glucose levels (BGL) were low in 9 respondents (20%), moderate in 15 respondents (35%), and high in 20 respondents (45%). After the exercises, BGL were low in 29 respondents (66%), moderate in 10 respondents (23%), and high in 5 respondents (11%). The Wilcoxon Test results indicated a p-value < 0.05, specifically p=0.009, thereby accepting H1. Nurses are encouraged to include diabetes mellitus exercises as part of hyperglycemia management programs, especially to enhance the effectiveness of blood glucose control. Further research with larger sample sizes and extended intervention durations is recommended to strengthen these findings.